Biaxially stretched cigarette film and preparation method thereof
By using the combination of polybutylene succinate, toughener, slip agent and nano calcium carbonate in the smoke film, the problem of difficulty in degradation and poor toughness of the polypropylene film is solved, and the tensile strength of the smoke film is improved and degradation performance, achieving environmentally friendly cigarette packaging.
Patent Information
- Application Number
- CN202211676396.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-12-26
AI Technical Summary
Bidirectional tensile polypropylene film is difficult to degrade, resulting in white pollution and excessive consumption of petroleum resources. At the same time, polybutylene succinate is poorly tough and prone to fracture when blown, making it difficult to meet the standards of smoke film.
Using a combination of polybutylene succinate, toughener, slip agent, nano calcium carbonate and hydrogenated petroleum resin, a two-way stretched smoke film is prepared through a twin-screw extrusion mechanism to control the melt extrusion temperature and stretching process. , increase toughness and reduce the risk of fracture.
It improves the tensile strength and toughness of the smoke film, reduces the risk of fracture, avoids white pollution, and enhances the degradation performance of the smoke film. It is suitable for cigarette packaging.
Smart Images

Figure BDA0004018385680000031 
Figure BDA0004018385680000041 
Figure BDA0004018385680000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cigarette films, and in particular to a biaxially stretched cigarette film and a preparation method thereof. Background Art
[0002] Biaxially oriented polypropylene film has the advantages of good transparency, good dimensional stability, high mechanical strength, and strong water vapor barrier ability. It is widely used in cigarette film, which plays a moisture-proof role for cigarette boxes. Due to the large amount of cigarette film used and the inability of polypropylene to degrade, polypropylene cigarette film brings a lot of white pollution and consumes a lot of petroleum resources.
[0003] Polybutylene succinate (PBS) is a polymer compound, and its structural unit contains an ester group that is easily hydrolyzed. Under conditions such as composting and contact with specific microorganisms, it is easily decomposed and metabolized by a variety of microorganisms in nature or enzymes in animals and plants, and finally forms CO2 and H2O, thus avoiding environmental pollution. Polybutylene succinate is a polymer with good biodegradability. Compared with biodegradable plastics such as polylactic acid, polyhydroxyalkanoate, and polycaprolactone, PBS is relatively cheap, has good heat resistance, and a heat deformation temperature of nearly 100°C. It is the focus of research and development of biodegradable plastics at home and abroad.
[0004] However, during the research process, the applicant found that the use of polybutylene succinate in cigarette film can solve the problem that biaxially oriented polypropylene film cannot be degraded. However, polybutylene succinate (PBS) has poor toughness and poor film blowing performance. It is easy for the film to have poor tensile properties and breakage during film blowing, making it difficult to meet the standards for cigarette film. Summary of the invention
[0005] In order to improve the stretching properties of a cigarette film, the present application provides a biaxially stretched cigarette film and a preparation method thereof.
[0006] In a first aspect, the present application provides a method for preparing a biaxially stretched cigarette film, which is implemented by the following technical solution:
[0007] A method for preparing a biaxially stretched cigarette film comprises the following steps:
[0008] S1. After drying, polybutylene succinate, toughening agent, lubricant, nano calcium carbonate and hydrogenated petroleum resin are respectively placed in a silo and fed into a twin-screw extruder according to a mass ratio of (80-120):(4-7):(3-5):(2-4):(1-2). The melt extrusion temperature is controlled at 140-180° C. and the sheets are cast through a casting roller at a temperature of 25-35° C. to form a sheet;
[0009] S2, biaxial stretching: preheat the sheet and then stretch it longitudinally, cool it down and set it, then preheat it again and stretch it transversely, cool it down and set it;
[0010] S3, after corona treatment, winding, aging and slitting, a biaxially stretched cigarette film is obtained.
[0011] By adopting the above technical scheme, the toughening agent and the lubricant are extensible, easy to pull but not easy to break. The addition of the toughening agent and the lubricant can improve the toughness of polybutylene succinate, improve the film blowing performance of polybutylene succinate, and make it not easy to break after biaxial stretching, thereby improving the tensile strength of the cigarette film and reducing the "breakage" phenomenon of the cigarette film during the packaging process.
[0012] The melt extrusion temperature is controlled at 140-180°C. The melt temperature is not too high, so it is not easy to reduce the longitudinal tensile strength of the film.
[0013] Preferably, the toughening agent is prepared by mixing polyvinyl alcohol and ethylene-vinyl acetate copolymer in a mass ratio of 1:(2-3).
[0014] The compound of polyvinyl alcohol and ethylene-vinyl acetate copolymer is used as a toughening agent, which not only improves the tensile strength of the cigarette film, but also prevents the elongation at break of the cigarette film from being too high, so that the elongation at break of the cigarette film meets the requirements of the cigarette packaging industry, and the transverse elongation at break is below 80%. In this way, the cigarette film packaging is easier to cut when it is loaded on the machine, thereby increasing the smoothness of the production process.
[0015] Preferably, the polyvinyl alcohol is PVA2099.
[0016] The appropriate degree of polymerization of PVA2099 can not only improve the tensile strength of the cigarette film, but also reduce the elongation at break of the cigarette film to a lesser extent, so that the elongation at break of the cigarette film is within an appropriate range.
[0017] Preferably, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 25 wt%.
[0018] The ethylene-vinyl acetate copolymer with a vinyl acetate content of 25wt% has a low degree of crystallinity and a high flexibility, which not only improves the toughness of polybutylene succinate, further improves the tensile strength of the cigarette film, but also improves the heat sealing performance of the cigarette film. The heat sealing strength of the cigarette film of the present application is above 5.0N / 15mm, which greatly improves the cigarette film packaging speed.
[0019] Preferably, the lubricant is prepared by mixing ethylene bisstearic acid amide and behenic acid amide in a mass ratio of (1.5-2.5):1.
[0020] The combination of ethylene bisstearamide and behenamide as a lubricant is not only beneficial to the injection molding of polybutylene succinate, but also improves the lubricity of the cigarette film, reduces the occurrence of scratches caused by friction with the machine during the packaging process, improves the appearance of the cigarette film, and can also improve the tensile strength and heat-sealing performance of the cigarette film, without the phenomenon of loose heat sealing, flying bags, wrinkles, etc.
[0021] Preferably, the mass ratio of ethylene bisstearamide to behenic acid amide is 2:1.
[0022] When the mass ratio of ethylene bisstearamide and behenic acid amide is 2:1, the cigarette film has higher tensile strength and better heat sealing performance.
[0023] Preferably, the mass ratio of the polybutylene succinate, toughening agent, lubricant, nano-calcium carbonate and hydrogenated petroleum resin is 100:6:4:3:1.5.
[0024] When the mass ratio of polybutylene succinate, toughening agent, lubricant, nano-calcium carbonate and hydrogenated petroleum resin is 100:6:4:3:1.5, the biaxially oriented cigarette film has higher tensile strength and excellent gloss. This is because nano-calcium carbonate and hydrogenated petroleum resin improve the dispersibility of the system, especially the dispersibility of polybutylene succinate and toughening agent.
[0025] Preferably, in the step S2, the specific operation of the biaxial stretching includes:
[0026] S21, preheating the sheet at 60-80°C, longitudinally stretching at 70-90°C, and cooling and shaping at 0-10°C;
[0027] S22, preheating the longitudinally stretched, cooled and shaped sheet at 70-90°C, stretching it transversely at 90-110°C, and cooling and shaping it at 0-10°C.
[0028] Preferably, in the step S1, the screw speed of the twin-screw extruder is 200-400 rpm.
[0029] In the second aspect, the present application provides a biaxially stretched cigarette film, which is implemented by the following technical solution:
[0030] A biaxially stretched cigarette film prepared by the above preparation method.
[0031] The biaxially oriented cigarette film prepared in the present application is not only easy to degrade and avoid white pollution, but also not easy to break after biaxially oriented and has high tensile strength.
[0032] In summary, this application has the following beneficial effects:
[0033] 1. The biaxially oriented cigarette film prepared in the present application is not only easy to degrade and avoid white pollution, but also not easy to break after biaxial stretching and has high tensile strength.
[0034] 2. The present application adopts a compound of polyvinyl alcohol and ethylene-vinyl acetate copolymer as a toughening agent, which not only improves the tensile strength of the cigarette film, but also makes the transverse elongation at break of the cigarette film below 80%.
[0035] 3. The present application uses ethylene bisstearamide and behenic acid amide as a lubricant, which is not only beneficial to the injection molding of polybutylene succinate, but also improves the lubricity of the cigarette film and further improves the tensile strength of the cigarette film. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] Example
[0038] Embodiments 1-16 provide a biaxially stretched cigarette film, which is described below using Embodiment 1 as an example.
[0039] The biaxially oriented cigarette film provided in Example 1 is prepared in the following steps:
[0040] S1. After drying, polybutylene succinate, toughening agent, lubricant, nano calcium carbonate and hydrogenated petroleum resin are respectively placed in a silo and fed into a twin-screw extruder at a mass ratio of 80:4:3:2:1. The melt extrusion temperature is controlled at 140°C and the screw speed is 200 rpm. The sheets are cast by a casting roller at a temperature of 25°C to form a sheet.
[0041] S2, biaxial stretch;
[0042] S21, preheating the sheet at 60°C, longitudinally stretching it 5 times at 70°C, and cooling and shaping it at 10°C;
[0043] S22, preheating the longitudinally stretched, cooled and shaped sheet at 70°C, stretching it 5 times transversely at 90°C, and cooling and shaping it at 10°C;
[0044] S3, after corona treatment, winding, aging, and slitting into biaxially stretched cigarette films with a thickness of 20 μm;
[0045] Among them, the toughening agent is PVA1788;
[0046] The lubricant is ethylene bisstearamide.
[0047] The only difference between Examples 1-5 and Example 1 is that the reaction process parameters are different, as shown in Table 1.
[0048] Table 1 Reaction process parameters of Examples 1-5
[0049]
[0050]
[0051] Example 6 is different from Example 5 only in that the mass ratio of polybutylene succinate, toughening agent, lubricant, nano-calcium carbonate and hydrogenated petroleum resin is 120:7:5:4:2.
[0052] Example 7 is different from Example 5 only in that the mass ratio of polybutylene succinate, toughening agent, lubricant, nano-calcium carbonate and hydrogenated petroleum resin is 100:6:4:3:1.5.
[0053] Example 8 is different from Example 7 only in that the toughening agent is ethylene-vinyl acetate copolymer 550, the content of vinyl acetate is 15wt%.
[0054] Example 9 is different from Example 7 only in that the toughening agent is PVA1788 and ethylene-vinyl acetate copolymer A mixture of 550, PVA1788 and ethylene-vinyl acetate copolymer The mass ratio of 550 is 1:2.
[0055] Example 10, the only difference from Example 9 is that PVA1788 and ethylene-vinyl acetate copolymer The mass ratio of 550 is 1:3.
[0056] Example 11 is different from Example 10 only in that PVA1788 is replaced by PVA2099.
[0057] Example 12 is different from Example 11 only in that: ethylene-vinyl acetate copolymer 550 and other quality replaced by 350 (vinyl acetate content is 25wt%).
[0058] Example 13 is different from Example 12 only in that the lubricant is behenic acid amide.
[0059] Example 14 is different from Example 13 only in that the lubricant is a mixture of ethylene bisstearic acid amide and behenic acid amide, and the mass ratio of ethylene bisstearic acid amide to behenic acid amide is 1.5:1.
[0060] Example 15 is different from Example 14 only in that the mass ratio of ethylene bisstearamide to behenic acid amide is 2.5:1.
[0061] Example 16 is different from Example 14 only in that the mass ratio of ethylene bisstearamide to behenic acid amide is 2:1.
[0062] Comparative Example
[0063] Comparative Example 1 is different from Example 1 only in that PVA1788 is not added.
[0064] Comparative Example 2 is different from Example 1 only in that ethylene bisstearamide is not added.
[0065] Performance testing
[0066] The following performance tests were performed on the biaxially stretched cigarette films prepared in Examples 1-16 and Comparative Examples 1-2 of the present application.
[0067] 1. Tensile strength: The longitudinal tensile strength and transverse tensile strength of the biaxially stretched cigarette films of Examples 1-16 and Comparative Examples 1-2 were tested with reference to GB / T1040.3 “Test for tensile properties of plastics”. The test results are shown in Table 2.
[0068] 2. Elongation at break: The longitudinal elongation at break and the transverse elongation at break of the biaxially stretched cigarette films of Examples 1-16 and Comparative Examples 1-2 were tested with reference to GB / T1040.3 “Test for tensile properties of plastics”. The test results are shown in Table 2.
[0069] Table 2 Test results
[0070]
[0071] The following describes the present application in detail with respect to the test data in Table 2.
[0072] It can be seen from the test data of Example 1 and Comparative Example 1 that the addition of toughening agent PVA1788 in the present application significantly improves the tensile strength of the biaxially stretched cigarette film.
[0073] From the test data of Example 1 and Comparative Example 2, it can be seen that the addition of ethylene bisstearamide in the present application improves the tensile strength of the biaxially stretched cigarette film.
[0074] It can be seen from the test data of Examples 3 and 4 that increasing the temperature of biaxial stretching can increase the tensile strength of the biaxially stretched cigarette film and reduce the elongation at break of the biaxially stretched cigarette film.
[0075] It can be seen from the test data of Example 4 and Example 5 that lowering the cooling and setting temperature after biaxial stretching is beneficial to accelerating the cooling speed, thereby improving the tensile strength of the biaxially stretched cigarette film. However, when the cooling and setting temperature is 0°C, the transverse elongation at break of the biaxially stretched cigarette film is higher than 80%, and the biaxially stretched cigarette film is not easy to cut when being packaged on the machine, which will reduce the smoothness of the production process.
[0076] From the test data of Example 7 and Examples 5 and 6, it can be seen that when the mass ratio of polybutylene succinate, toughening agent, lubricant, nano-calcium carbonate and hydrogenated petroleum resin is 100:6:4:3:1.5, the tensile strength of the biaxially stretched cigarette film is higher.
[0077] From the test data of Example 9 and Examples 7 and 8, it can be seen that the toughening agent in Example 7 is PVA1788, the toughening agent in Example 8 is ethylene-vinyl acetate copolymer, and the toughening agent in Example 9 is a compound of PVA1788 and ethylene-vinyl acetate copolymer, which further improves the tensile strength of the cigarette film and makes the transverse elongation at break of the cigarette film below 80%.
[0078] From the test data of Example 11 and Example 10, it can be seen that the plasticizer in Example 10 is PVA1788 and ethylene-vinyl acetate copolymer. 550, the plasticizer in Example 11 is PVA2099 and ethylene-vinyl acetate copolymer 550, the polymerization degree of PVA2099 is higher than that of PVA1788. PVA2099 can not only improve the tensile strength of the cigarette film, but also reduce the elongation at break of the cigarette film to a lesser extent, so that the elongation at break of the cigarette film is within an appropriate range.
[0079] From the test data of Example 12 and Example 11, it can be seen that the plasticizer in Example 12 is PVA2099 and ethylene-vinyl acetate copolymer. 350 compound, ethylene-vinyl acetate copolymer The content of vinyl acetate in 350 is 25wt%, and the plasticizer in Example 11 is PVA2099 and ethylene-vinyl acetate copolymer 550 compound, ethylene-vinyl acetate copolymer The content of vinyl acetate in 550 is 15wt%, ethylene-vinyl acetate copolymer The vinyl acetate content of 350 is higher than that of ethylene-vinyl acetate copolymer 550% vinyl acetate content, ethylene-vinyl acetate copolymer 350 has lower crystallinity and higher flexibility, which not only improves the toughness of polybutylene succinate, but also further improves the tensile strength of the cigarette film.
[0080] From the test data of Example 14 and Examples 12 and 13, it can be seen that the combination of ethylene bisstearamide and behenic acid amide as a lubricant is not only beneficial to the injection molding of polybutylene succinate, but also improves the lubricity of the cigarette film and further improves the tensile strength of the cigarette film.
[0081] It can be seen from the test data of Example 16 and Examples 14 and 15 that when the mass ratio of ethylene bisstearamide to behenic acid amide is 2:1, the tensile strength of the cigarette film is higher.
[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a biaxially stretched cigarette film, characterized in that: The steps include: S1. After drying, polybutylene succinate, toughening agent, lubricant, nano calcium carbonate and hydrogenated petroleum resin are respectively placed in a silo and fed into a twin-screw extruder according to a mass ratio of (80-120):(4-7):(3-5):(2-4):(1-2). The melt extrusion temperature is controlled at 140-180°C and the sheets are cast through a casting roller at a temperature of 25-35°C to form sheets. S2, biaxial stretching: preheat the sheet and then stretch it longitudinally, cool it down and set it, then preheat it again and stretch it transversely, cool it down and set it; S3, after corona treatment, rolling, aging, and slitting, a biaxially stretched cigarette film is obtained; The toughening agent is prepared by mixing polyvinyl alcohol and ethylene-vinyl acetate copolymer in a mass ratio of 1:(2-3), wherein the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 25wt%; The lubricant is prepared by mixing ethylene bis stearic acid amide and behenic acid amide in a mass ratio of (1.5-2.5):
1.
2. The method for preparing a biaxially oriented cigarette film according to claim 1, characterized in that: The polyvinyl alcohol is PVA2099.
3. The method for preparing a biaxially oriented cigarette film according to claim 1, characterized in that: The mass ratio of the ethylene bisstearic acid amide to the behenic acid amide is 2:
1.
4. The method for preparing a biaxially oriented cigarette film according to claim 1, characterized in that: The mass ratio of the polybutylene succinate, toughening agent, lubricant, nano calcium carbonate and hydrogenated petroleum resin is 100:6:4:3:1.
5.
5. The method for preparing a biaxially oriented cigarette film according to claim 1, characterized in that: In the step S2, the specific operation of the biaxial stretching includes: S21, preheating the sheet at 60-80°C, longitudinally stretching at 70-90°C, and cooling and shaping at 0-10°C; S22, preheating the longitudinally stretched, cooled and shaped sheet at 70-90°C, stretching it transversely at 90-110°C, and cooling and shaping it at 0-10°C.
6. The method for preparing a biaxially oriented cigarette film according to claim 1, characterized in that: In the step S1, the screw speed of the twin-screw extruder is 200-400 rpm.
7. A biaxially stretched cigarette film prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Degradable biaxially-oriented polylactic acid cigarette film and preparation method thereof
CN110774714A
Biaxially-oriented biodegradable polyester composite heat-sealing film as well as preparation method and application thereof
CN114193891A